2019
DOI: 10.1186/s12934-019-1088-y
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of poly (3-hydroxyalkanoate) depolymerase gene and overexpression of three poly (3-hydroxybutyrate) biosynthetic genes improve poly (3-hydroxybutyrate) production from nitrogen rich medium by Rhodobacter sphaeroides

Abstract: Background Due to various environmental problems, biodegradable polymers such as poly (3-hydroxybutyrate) (PHB) have gained much attention in recent years. Purple non-sulfur (PNS) bacteria have various attractive characteristics useful for environmentally harmless PHB production. However, production of PHB by PNS bacteria using genetic engineering has never been reported. This study is the first report of a genetically engineered PNS bacterial strain with a high PHB production. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…The PhaZ gene, which mediates PHB depolymerization, is downregulated during the active growth phase by PhaR, a regulator protein of phaZCPR operon [5]. Recent studies revealed that disruption of the PhaZ gene and overexpression of the PhaA, PhaB, and PhaC genes elevated PHB production in R. sphaeroides [18]. Moreover, PHB biosynthetic enzymes, including PhaC, which is the limiting step for PHB production in R. sphaeroides, altered their activities very easily in response to changes in the external environment [18,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PhaZ gene, which mediates PHB depolymerization, is downregulated during the active growth phase by PhaR, a regulator protein of phaZCPR operon [5]. Recent studies revealed that disruption of the PhaZ gene and overexpression of the PhaA, PhaB, and PhaC genes elevated PHB production in R. sphaeroides [18]. Moreover, PHB biosynthetic enzymes, including PhaC, which is the limiting step for PHB production in R. sphaeroides, altered their activities very easily in response to changes in the external environment [18,50].…”
Section: Discussionmentioning
confidence: 99%
“…Among various carbon sources, acetate yielded the highest PHB production [17]. Moreover, PHB productivity can be greatly improved within R. sphaeroides, since it is possible to enhance the performance of strains using well-established genetic engineering tools and by integrating advances in previous studies [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Besides PHA synthases for biopolymer production, these bacteria can produce PHA depolymerases to initiate its metabolization. To prevent PHA degradation, the PHA depolymerase(s) could be knocked out, as was done for Pseudomonas putida KT2442 and Rhodobacter sphaeroides HJ [32,33]. PHA content in cell dry mass (wt%)…”
Section: Culture Growth and Pha Production By The Mixed Microbial Conmentioning
confidence: 99%
“…Although R. sphaeroides HJ was recently used as a host bacterium for polyhydroxyalkanoate production instead of hydrogen (2), its genome has not yet been sequenced. To make research on R.…”
Section: Announcementmentioning
confidence: 99%